Penerapan Metode Servqual Dalam Penentuan Tingkat Kepuasan Pelayanan Masyarakat Di Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Deli Serdang - Nita Susanti Br Perangin-Angin; Preddy Marpaung (JURNAL MAHAJANA INFORMASI, 2021)
Service serves to help the needs of others by providing convenience in meeting all the necessary needs. In carrying out service activities, public service providers are one of the main functions in good governance. In the field of government, service issues play an important role because they involve the public interest and the interests of the entire community, and the quality of service becomes a benchmark for evaluating an agency. Every public service provider institution is required to provide the best service for the community, fast, precise service and meet the needs of the community so that people are satisfied with the services they get. One of the government agencies in the field of public services is the Department of Population and Civil Registry of Deli Serdang Regency. This study uses a decision support system using the Servqual (Service Quality) method in determining the level of satisfaction of community services at the Department of Population and Civil Registration of Deli Serdang Regency. This study uses five main dimensions, namely tangibles or physical evidence, Reliability or reliability, Responsiveness or responsiveness, Assurance or certainty and certainty, and Empathy. This study uses 9 alternative data as service test materials. The results of this study indicate that KK services get very satisfactory results, marriage certificate citation services, death certificate citations, and online population data get satisfactory results, KK services, transfer certificates, birth certificate citations, child identity cards. , and divorce certificates get satisfactory results.